How can r = 6c + 2t be solved?
You have provided an equation r = 6c + 2t.
This equation has 2 variables c and t and r is dependent on their values. There is no further information provided about either of them.
It is not possible to solve for either of the variables using just this information.
If we were to take two of these values as constants, the third can be expressed as a relation of the constants. For example:
r = 6c + 2t , where c and t are constants.
c = (r - 2t)/6, where r and t are constants.
t = ( r - 6c)/2, where r and c are constants.
To solve for the three variables r, c and t, we require three relations between the given variables which can be translated into three equations.